MINERALOGICAL AND SPECTROSCOPIC FEATURES OF Pt ARSENIDES OF PAY-KHOY Cu-Ni OCCURRENCES (NENETS AUTONOMOUS OKRUG) - R.I. Shaybekov; S.I. Isaenko; E.M. Tropnikov (Минералогия)
The paper considers the mineralogical and spectroscopic features of sperrylite, which is a main Pt source of low-sulfide Pt-bearing Cu–Ni occurrences of the Devonian Pay-Khoy sills. Platinum arsenides occur in silicates/oxides, sulfides and at contacts between sulfides and silicates/oxides. Raman spectroscopic studies shown that Raman spectrum of anhedral sperrylite inclusions and individual crystals exhibit two (210–214 and 274–277 cm–1) and three (208–214, 219–223 and 272– 277 cm–1) intense bands, respectively. According to paragenetic assemblage, sperrylite was formed at temperatures of